Suomalaisvanhempien vanhemmuustyyliprofiilit ja niiden yhteydet lasten kaltoinkohteluun COVID-19-poikkeusaikana - Ahola, Jonna; Talme, Meri (2024)
The aim of this study was to examine the parenting style profiles present among Finnish parents and how they are associated with child maltreatment during the COVID-19 pandemic. Furthermore, it was explored how the parenting style profiles are related to family structure, parental age, gender, educational attainment and employment situation and whether the profiles differ in relation to child maltreatment even after controlling for the background variables. The data was gathered via a Webropol-survey in the spring of 2020 as a part of VoiKu-COVID-19-research project, which is a part of the broader International Investigation of Parental Burnout (IIPB) consortium. The participants of the present study were 984 parents (88.3 % mothers) whose ages ranged from 22 to 60. The data was analysed with K-means cluster analysis, one-way Analysis of Variance (ANOVA), cross tabulation, chi-squared test, Kruskal-Wallis test and Analysis of Covariance (ANCOVA). As a result, six parenting style profiles were found: authoritative (20.9 %), permissive (18.4 %), controlling (15.9